2021
DOI: 10.1002/mco2.83
|View full text |Cite
|
Sign up to set email alerts
|

Lomerizine 2HCl inhibits cell proliferation and induces protective autophagy in colorectal cancer via the PI3K/Akt/mTOR signaling pathway

Abstract: Colorectal cancer (CRC) is one of the most common malignancies currently. Despite advances in drug development, the survival and response rates in CRC patients are still poor. In our previous study, a library comprised of 1056 bioactive compounds was used for screening of drugs that could suppress CRC. Lomerizine 2HCl, which is an approved prophylactic drug for migraines, was selected for our studies. The results of in vitro and in vivo assays suggested that lomerizine 2HCl suppresses cell growth and promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The Akt/mTOR signaling is the main negative regulator of autophagy, and participates in regulating tumor proliferation [16,45]. In the present study, OXI restrained the Akt/mTOR axis, as demonstrated by the decreased phosphorylation levels of Akt and mTOR.…”
Section: Discussionsupporting
confidence: 59%
“…The Akt/mTOR signaling is the main negative regulator of autophagy, and participates in regulating tumor proliferation [16,45]. In the present study, OXI restrained the Akt/mTOR axis, as demonstrated by the decreased phosphorylation levels of Akt and mTOR.…”
Section: Discussionsupporting
confidence: 59%
“…Gene profiles were analyzed by the DESeq R software package (1.10.1), and genes with a fold change >2 were deemed differentially expressed genes. [ 2 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] In addition to the high incidence, the limited choice of chemotherapeutic drugs also contributes to the high mortality rate of CRC patients. [ 2 ] There is an urgent need to develop effective and low‐toxicity drugs to combat CRC. More than 90% of CRC patients have constitutive activation of the Wnt/ β ‐catenin pathway due to adenomatous polyposis coli (APC) or β ‐catenin mutations, which disrupts the cytoplasmic β ‐catenin destruction complex and leads to the nuclear translocation of β ‐catenin.…”
Section: Introductionmentioning
confidence: 99%
“… 197 Meanwhile, an inhibition of the PI3K–AKT signaling axis can sensitize cancer cells to induce ferroptosis. 198 This sensibility requires the help of mTOR that is also the important downstream molecule of AMPK signaling pathway. 110 In xenograft mouse models for PI3K‐mutated breast cancer and PTEN‐defective prostate cancer, the combination of mTORC1 inhibition with ferroptosis induction resulted in near‐complete tumor regression.…”
Section: Molecular Signaling Pathways On Vcmentioning
confidence: 99%
“…Recent study has proved that glucagon‐like peptide‐1 exerted multiple cardioprotective functions such as regulation of osteoblastic transformation and calcification of VSMCs through the activation of PI3K‐AKT signaling 197 . Meanwhile, an inhibition of the PI3K–AKT signaling axis can sensitize cancer cells to induce ferroptosis 198 . This sensibility requires the help of mTOR that is also the important downstream molecule of AMPK signaling pathway 110 .…”
Section: Molecular Signaling Pathways On Vcmentioning
confidence: 99%